Smart cities and Sustainable Development: literature review and prospects for future research - Genari, Denise (2018)
The accelerated process of urbanization of society is accompanied by challenges associated with social, environmental and economic spheres. In this context, emphasis is placed on the emergence of the smart cities theme, which means spaces where the adequate use of the available infrastructure occurs, with the objective of improving economic and political efficiency, allowing social, cultural and urban development. Based on this perspective, the main objective of this article is to characterize the studies that link the themes of smart cities and sustainable development, in addition to identifying future research opportunities.To this end, a systematic review of the literature was carried out using the Alceste software support. The main results point to the predominance of studies based on qualitative research, primarily addressing the environmental dimension of sustainability and the systemic dimension related to smart cities, including information and communication technologies. Based on these findings, it is recommended that future research should be carried out also taking into consideration the social and economic dimension of sustainability.